Innovation dynamics in greenhouse tomato (Solanum lycopersicum) production in Puebla, Mexico - Mundo Coxca, Misael; Jaramillo Villanueva, J. Luis; Barrera Rodríguez, A. Isabel (Agricultura, Sociedad y Desarrollo, 2022)
The use of technological innovations in greenhouse vegetable growing translates into high yields to the producers. This study analyzes the innovation adoption index (InAI) in tomato production units (TPUs) under greenhouses in the municipalities of Aquixtla, Tetela de Ocampo, Tecamachalco and Tochtepec, state of Puebla and its relationship with the crop’s yield, in addition to understanding the stakeholders implicit in the dissemination of innovations through a social networks analysis. Interviews (103) were applied to producers in the second semester of 2017, using a structured questionnaire. A global InAI of 36% was obtained, highlighting the components of health and nutrition that showed an InAI of 57%. The social networks analysis showed that learning about innovations is done primarily between producers despite not having a formal organization. Private technical assistance is responsible for technology transfer in the TPUs, which is why it is important for decision makers and particularly for producers, by generating formal communication channels that allow exchanging experiences and fostering learning as a whole, with the aim of increasing the InAI and consequently improving the yield of TPUs in the state.